Strategi Komunikasi Pemasaran Moogs Coffee Melalui Media Sosial Instagram - Nisfa Alfiya Sofiyani; Anita Agustina Wulandari (DIGICOM : Jurnal Komunikasi dan Media, 2023)
This study aims to determine the marketing communication strategy of Moogs Coffee through Instagram social media. The theory used is the theory of Integrated Marketing Communication (IMC). This theory is related to the development and implementation process as a form of persuasive communication program to customers and prospective customers on an ongoing basis. The type of research used is qualitative research. By using the interview method in data collection. Interview informants for this research were Operational Manager Moogs Coffee, Creative Content Manager Moogs Coffee, and visitors to Moogs Coffee. Based on the research that has been done, the researcher concludes that the strategy implemented by Moogs Coffee is said to be running well because almost all aspects of the theory have been implemented. This has a positive impact and shows the reaction of the followers or customers of Moogs Coffee.